2015
DOI: 10.1111/ajgw.12149
|View full text |Cite
|
Sign up to set email alerts
|

Aroma composition of 2-year-old New Zealand Pinot Noir wine and its relationship to sensory characteristics using canonical correlation analysis and addition/omission tests

Abstract: Background and Aims:Relationships between the chemical composition and the sensory perception of red wines are generally poorly understood. In New Zealand, the vineyard area of Pinot Noir has increased markedly and wines from this red cultivar now constitute a significant proportion of total production. The aim of this study was to identify aroma compounds of major sensory significance in New Zealand Pinot Noir wines. Methods and Results: The concentration of 34 aroma chemicals in 32 New Zealand Pinot Noir win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 65 publications
1
48
0
Order By: Relevance
“…The extreme exception of linalool in Pinot Noir (85 ÎŒg/L from 48 analyses) reflects a high concentration of linalool found in 32 regional New Zealand wines using the SIDA method (Tomasino et al . ). Despite this high concentration of linalool, the authors noted it was not implicated in the two strongest canonical correlations found in the article (black cherry/blackberry/plum aroma or jam/oak aroma and spice flavour).…”
Section: Monoterpenes In Grapes and Winementioning
confidence: 97%
“…The extreme exception of linalool in Pinot Noir (85 ÎŒg/L from 48 analyses) reflects a high concentration of linalool found in 32 regional New Zealand wines using the SIDA method (Tomasino et al . ). Despite this high concentration of linalool, the authors noted it was not implicated in the two strongest canonical correlations found in the article (black cherry/blackberry/plum aroma or jam/oak aroma and spice flavour).…”
Section: Monoterpenes In Grapes and Winementioning
confidence: 97%
“…In particular, phenolic compounds play primary roles in the color, taste and astringency, whereas wine flavor and aroma is essentially determined by the volatile profile [ 8 , 9 ]. Regarding their biosynthetic pathways, phenolic compounds in grape berries are produced through phenylpropanoid-flavonoid metabolism that begins with phenylalanine, whereas volatile compounds are synthesized via multiple pathways that starts from isoprenes, amino acids, and polyunsaturated fatty acids [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it would be interesting to validate the potential drivers of minerality found in the different studies. Classical addition or omission studies using neutral or synthetic wines [68,70,71] could be an interesting sensory strategy to carry out this validation. In terms of a further novel direction, perception of saltiness and salinity in wine appear to be taking on a new significance in taste perceptions and could form the basis of interesting future research.…”
Section: Overall Conclusionmentioning
confidence: 99%